Engendering Governance After Armed Conflict: Observations From Kosovo - Holzner, Brigitte M. (Frontiers in Sociology, 2021)
Gender-responsive governance after armed conflict: Observations from Kosovo B. M. Holzner Affiliate of the Herbert Kelman Institute for Interactive Conflict Resolution This paper addresses gender-responsive governance reforms in post-conflict Kosovo from two perspectives: 1) the perspective of human rights as fundament for state-building, and 2) the resolutions of the UN Security Council regarding Women, Peace and Security, notably the initial UNSCR 1325. Special focus is laid on women’s agency in governance matters – at the level of the state and at the level of civil society. A gender approach to three dimensions of governance - political-administrative governance, security governance, and socioeconomic governance shows successes and problems in this post-conflict society. Special attention is given to the strategies of the women’s movement in reaching gender-responsive governance. Key words: gender governance, equality, post-conflict, state-building, security, CEDAW UNSCR 1325